2020
DOI: 10.1192/bjo.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dissociation on the effectiveness of psychotherapy for post-traumatic stress disorder: meta-analysis

Abstract: Background Many patients with post-traumatic stress disorder (PTSD) experience dissociative symptoms. The question of whether these dissociative symptoms negatively influence the effectiveness of psychotherapy for PTSD is unresolved. Aims To determine the influence of dissociative symptoms on psychotherapy outcome in PTSD. Method We conducted a systematic search in Cochrane, Embase, PILOTS, PsycINFO, PubMed and Web of Science for relevant clinical trials. A random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
3
31
1
1
Order By: Relevance
“…These findings are in line with studies on psychological dissociative symptoms (see [ 7 ]), in that dissociative symptoms do not seem to have a significant impact on the decrease in PTSD symptoms when trauma-focused therapy is administered without treating dissociative symptoms first. To our knowledge, this is the first study that extends these meta-analytic findings to somatoform dissociation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with studies on psychological dissociative symptoms (see [ 7 ]), in that dissociative symptoms do not seem to have a significant impact on the decrease in PTSD symptoms when trauma-focused therapy is administered without treating dissociative symptoms first. To our knowledge, this is the first study that extends these meta-analytic findings to somatoform dissociation.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, other studies found that dissociative symptoms did not predict trauma-focused treatment efficacy [ 5 , 6 ]. A recent meta-analysis showed that dissociation had no significant effect on treatment outcome, and that the impact of dissociation was about zero [ 7 ]. Additionally, some studies found that direct trauma-focused therapy actually led to a decrease in dissociative symptoms, e.g., [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants in this study were gender-matched and shown to be a homogeneous group with no significant differences in pathology and trauma experiences between the age groups, with the exception of the dissociative subtype of PTSD, which was less prevalent in older adults, yet a similar outcome was also found in a previous study [ 45 ]. However, a recent meta-analysis found no evidence that dissociation symptoms moderate the effectiveness of psychotherapy for PTSD [ 46 ]. Another strength of the study was the use of common PTSD assessments and manualized, empirically-based treatment protocols with secured treatment fidelity, by supervision.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with some other NET studies and other TFT studies. 17,56,58 Also, a meta-analysis on the effect of dissociation suggests that pre-treatment dissociation does not determine trauma-focused psychotherapy outcomes in PTSD. 58 SMI symptoms were assessed with generic measures to allow for comparisons across diagnostic groups.…”
Section: Main Findingsmentioning
confidence: 99%
“…17,56,58 Also, a meta-analysis on the effect of dissociation suggests that pre-treatment dissociation does not determine trauma-focused psychotherapy outcomes in PTSD. 58 SMI symptoms were assessed with generic measures to allow for comparisons across diagnostic groups. 59 The coherence of the SMI outcomes was low: a slight improvement in SMI was seen based on HoNOS, there were no significant changes in perceived care needs (CAN) and quality of life (MANSA) based on self-reporting, and care providers concluded that global functioning (GAF) was significantly increased.…”
Section: Main Findingsmentioning
confidence: 99%